Spatio-temporal changes of small protist and free-living bacterial communities in a temperate dimictic lake: insights from metabarcoding and machine learning - Karlicki, Michał; Bednarska, Anna; Hałakuc, Paweł; Maciszewski, Kacper; Karnkowska, Anna (FEMS microbiology ecology, 2024)
Microbial communities, which include prokaryotes and protists, play an important role in aquatic ecosystems and influence ecological processes. To understand these communities, metabarcoding provides a powerful tool to assess their taxonomic composition and track spatio-temporal dynamics in both marine and freshwater environments. While marine ecosystems have been extensively studied, there is a notable research gap in understanding eukaryotic microbial communities in temperate lakes. Our study addresses this gap by investigating the free-living bacteria and small protist communities in Lake Roś (Poland), a dimictic temperate lake. Metabarcoding analysis revealed that both the bacterial and protist communities exhibit distinct seasonal patterns that are not necessarily shaped by dominant taxa. Furthermore, machine learning and statistical methods identified crucial amplicon sequence variants (ASVs) specific to each season. In addition, we identified a distinct community in the anoxic hypolimnion. We have also shown that the key factors shaping the composition of analysed community are temperature, oxygen, and silicon concentration. Understanding these community structures and the underlying factors is important in the context of climate change potentially impacting mixing patterns and leading to prolonged stratification.
Keywords: Biodiversity; taxonomické DNA čárové kódování; Temperature; Ecosystem; časoprostorová analýza; Lakes; mikrobiota; freshwater environments; Eukaryota; biodiverzita; Bacteria; Microbiota; DNA Barcoding, Taxonomic; protists; jezera; Machine Learning; prokaryotes; roční období; Seasons; temporal dynamics; stratification; ekosystém; abiotic factors; strojové učení; Spatio-Temporal Analysis; teplota